The Influence of Capital Expenditures and Investment on Economic Growth in West Nusa Tenggara Province 2012-2022 - Rizka Ridha Aulia; Wahyunadi, Wahyunadi; Eka Agustiani (Tinta Emas Publisher, 2024)
Economic growth is the process of a country's economic condition continuously moving towards a better condition over a certain period. Economic growth can also be interpreted as the process of increasing the production capacity of an economy which is realized in the form of an increase in national income. The aim of the research was to determine the effect of capital expenditure and investment on economic growth in West Nusa Tenggara Province. The method used in this research is the case study method and data collection in this research is by collecting information related to economic growth as seen from capital expenditure and investment. The research uses secondary data from 2012 to 2022 consisting of capital expenditure and investment data as well as economic growth. Data analysis techniques use the Multiple Linear Regression equation, t test, F test and coefficient of determination (R2). The research results show that capital expenditure has a positive but not significant effect on economic growth because it is based on the results of the regression with a tcount value smaller than ttable and a significance value greater than 0.05. The research results also show that investment has a positive and significant effect on economic growth. The coefficient of determination test results (R2) of 77.1% for capital expenditure and investment can explain economic growth and 22.9% is influenced by other variables not included in the research.